Characterization of the Functional Domain of β2-Microglobulin from the Asian Seabass, Lates calcarifer - Mohd-Padil, Hirzahida (Public Library of Science, 2010)

(untitled)
BACKGROUND: β2-Microglobulin (β(2)M) is the light chain of major histocompatibility class I (MHC I) that binds non-covalently with the α heavy chain. Both proteins attach to the antigen peptide, presenting a complex to the T cell to be destroyed via the immune mechanism. METHODOLOGY/PRINCIPAL FINDINGS: In this study, a cDNA sequence encoding β(2)M in the Asian seabass (Lates calcarifer) was identified and analyzed using in silico approaches to predict and characterize its functional domain. The β(2)M cDNA contains an open reading frame (ORF) of 351 bases with a coding capacity of 116 amino acids. A large portion of the protein consists of the IG constant domain (IGc1), similar to β(2)M sequences from other species studied thus far. Alignment of the IGc1 domains of β(2)M from L. calcarifer and other species shows a high degree of overall conservation. Seven amino acids were found to be conserved across taxa whereas conservation between L. calcarifer and other fish species was restricted to 14 amino acids at identical conserved positions. CONCLUSION/SIGNIFICANCE: As the L. calcarifer β(2)M protein analyzed in this study contains a functional domain similar to that of β(2)M proteins in other species, it can be postulated that the β(2)M proteins from L. calcarifer and other organisms are derived from a common ancestor and thus have a similar immune function. Interestingly, fish β(2)M genes could also be classified according to the ecological habitat of the species, i.e. whether it is from a freshwater, marine or euryhaline environment.